Analisis Keefektivan Aplikasi Grab Menggunakan Metode Heuristic Evaluation - Megawaty Megawaty; Della Avisa (UNIVERSITAS INDO GLOBAL MANDIRI, 2022)
Advances in science and technology that are increasingly rapidly and developing in today's era make users get business opportunities through technology media. Such as the use of trading media, service companies use internet media, which is currently not difficult to reach by all groups. One of these services is an online transportation service, namely Grab. The grab application can make grab-car orders, go-rides and not only that on the grab application. There is a menu for ordering go-food, pulses/tokens, cinema tickets, hotels, bills and others. This study aims to determine the effectiveness of the grab application used by the people of Palembang City. This grab application has been seen as a facility that provides convenience and convenience in ordering online based on user experience. The convenience and practicality provided are of course the reasons people use Grab services. For this reason, it is necessary to evaluate usability so that users do not experience difficulties in accessing the application, and also users can make repeated purchases. This evaluation is needed to improve the quality of the website, especially in terms of user experience to make it better, therefore the grab party must pay attention to the ease of users in accessing the grab application. The ease of accessing the application cannot be separated from the usability of a website. The Heuristic Evaluation method is a method that can be used to identify and explore Usability problems in the system under study.Keywords : Grab Application, Usabilitty, Heuristic Evaluation